Analisis Yuridis Hubungan Kerja Tenaga Kerja SPPG Tanpa Perjanjian Kerja Tertulis di Kabupaten Cirebon - Mohamad Irfandi; Irma Maulida (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the employment relationship status and legal protection for SPPG workers in the Free Nutritious Meal Program (MBG) in Cirebon Regency who work without written employment contracts. This research uses an empirical legal method with a juridical-sociological approach, examining labor law provisions and their implementation in practice. The results show that although there is no written employment agreement, the employment relationship between workers and foundations or implementing partners can still be legally recognized, as the essential elements of employment—work, wages and command—are fulfilled as stipulated in Law Number 13 of 2003 concerning Manpower. Additionally, workers' participation in the BPJS Employment program strengthens the administrative indication of an employment relationship. However, the absence of written contracts creates legal uncertainty and difficulties in evidence in the event of industrial disputes. Normatively, legal protection still exists, including rights to wages, working hours and social security, but in practice, such protection is not yet optimal. Therefore, strengthening administrative aspects through written employment agreements is necessary to ensure better legal certainty and protection for workers.